If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 5 = 13 + 4X Reorder the terms: 5 + 2X = 13 + 4X Solving 5 + 2X = 13 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 5 + 2X + -4X = 13 + 4X + -4X Combine like terms: 2X + -4X = -2X 5 + -2X = 13 + 4X + -4X Combine like terms: 4X + -4X = 0 5 + -2X = 13 + 0 5 + -2X = 13 Add '-5' to each side of the equation. 5 + -5 + -2X = 13 + -5 Combine like terms: 5 + -5 = 0 0 + -2X = 13 + -5 -2X = 13 + -5 Combine like terms: 13 + -5 = 8 -2X = 8 Divide each side by '-2'. X = -4 Simplifying X = -4
| a/8=13 | | 32-4x=6x+22 | | n-11=25 | | 2w+8x-11y+7w+4x+4y= | | 9x+6=3x-12 | | n/4+10 | | h-5=3*7 | | n-5=19 | | n+33=52 | | 6x-2x=12-4 | | 211-5x=40x+21 | | 5-10x=59-31x | | ln*5*X=3 | | 21/7+87/9(4+9) | | y(y+2)=3 | | 2(y-1)=4x+5 | | 4x=10x-24 | | 2(7b-1)33=19b | | 48-6x=21x+15 | | -4-7q+2q^2=0 | | -44-2x=10x-8x | | 7z+2-3z+5=15 | | F(14)=3(14)+2 | | (2x-5)/9-8(x+3)/3+4=5 | | 3-3x+4x-6=5x+1-x | | 8x-3=5(7-x) | | 6x+6=18-6x | | 2-x/4=1x/6 | | x^8-5=-5 | | (9x-2)/3-1(x+1)/7+3=9 | | 5(2x+1)-9=18 | | 2x+10+30+2x+x/30=360 |